Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan di Restoran Fastfood KFC di Kota Palembang - Geofany, Sheren; Sari, Fifinnela Winie; H, Heriyanto (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study was conducted to determine whether service quality and product quality affect customer satisfaction in Fastfood Restaurants.In this study has several problems such as limited questionnaire data collection, some respondents are less responsive. This study also determined the population and sample where the population was all customers of KFC Fastfood Restaurants in Palembang City and for the sample of 105 respondents. From the research that has been done, researchers draw conclusions that the data obtained is primary data. For sample acquisition using non-probability sampling techniques where this method is usually used for data processing using multiple linear analysis data processing using SPSS applications. This research shows the results that service quality, product quality have a positive influence on customer satisfaction at KFC Fastfood Restaurant in Palembang City.